Analisis Performansi Gear Pump Orisinil Dan Setelah 11.000 Jam Operasi Pada Unit Highlight B5+ Atlas Copco (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2021)
HighLight B5 + or what is generally called a tower lamp is a support tool that isusually used as a source of lighting during nighttime activities in a coal mine, and theHighLight B5 + is the latest generation of tower lamps where the hydraulic system is usedas a driver of tower poles. lamp, in the hydraulic system of this unit the gear pump is amajor component used and in general the longer the operating life of the gear pump willexperience a decrease in performance. From the problem of the decline in the performanceof the gear pump on the HighLight B5 + unit, I am interested in conducting a comparativeanalysis of performance and the purpose of this study is to determine the extent of thedecline in the performance of the hydraulic pump with the gear pump type of HighLight B5+ Atlas Copco after operating for 11,000 hours and provide information hydraulic systemwhich has now been applied to the tower lamp unit. The method used is quantitative byproviding information about the performance of the gear pump on the HighLight B5 +Atlas Copco unit, where the independent variable is the life time of the gear pump 11,000hours and the data collection process is carried out at the workshop of PT. Inti RayaAnugrahtama by conducting literature studies to find out the basic theory, workingprinciples and other supporting literature regarding the gear pump, observing data bymaking direct observations in the field in order to get more concrete data. The results ofthe analysis and discussion on the research of new gear pumps and those that have beenoperating for 11,000 hours show that the performance difference from the pressure of eachgear pump is 1.45 Psi / s and the average flow pressure is 0.1 Ltr / s.